The Sage handbook of educational leadership : advances in theory, research, and practice - 4 0 16; English, Fenwick W.; 5 (Thousand Oaks, California : Sage, 2005)
A comprehensive overview of educational leadership that explores a broad range of issues related to curriculum leadership, supervision, teacher evaluation, budgeting, planning, school design, principalship, and superintendency in the United States.
Includes bibliographical references and indexes.
Professional.
Keywords: 2 -- 0; 6; Educational leadership.;School supervision.;School administrators.;School superintendents and principals; 20; 2